TOPENG NASIONALISME PALSU: ANALISIS VIKTIMOLOGI DAN KRIMINOLOGI TINDAKAN KRIMINAL KORUPSI OLEH PEJABAT NEGARA - Appe Hutauruk; Fendi Maruba Parlindungan Hutahaean (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2026)
President Soekarno’s “JASMERAH” commemoration has now experienced a degradation of meaning in the hands of state actors trapped in the character of “Drunken God.” The phenomenon of White Collar Crime disguised as a “Mask of Nationalism” has mutated into a latent danger that threatens national sovereignty through policy conspiracies at the regional level. This study aims to deconstruct the mask of false nationalism and offer a legal argument that eradicating corruption without sacrificing remission is an absolute prerequisite for achieving constitutional national goals. The method used is a normative-prescriptive legal study by integrating legislative, conceptual, and victimological approaches as well as criminology. Data are analyzed descriptively and critically through deduction of legal syllogisms regarding regulations and jurisprudence on regional head corruption. The results of the study indicate that corruption has been institutionalized through the mechanism of “Politics of Revenge” after the Regional Head Election, which makes the people the main victims due to the loss of economic rights and general welfare. These findings conclude that the policy of amnesty for corruption perpetrators is a form of secondary victimization that strengthens the culture of impunity and betrays the constitutional mandate. As a solution, this study recommends a complete rejection of pardons, asset confiscation, and permanent revocation of political rights. This step is crucial to breaking the chain of corruption, restoring public trust, and restoring the government’s mandate to focus on the welfare of the people.